A 3D unstructured-grid model for Chesapeake Bay: Importance of bathymetry. (July 2018) - Ye, Fei; Zhang, Yinglong J.; Wang, Harry V.; Friedrichs, Marjorie A.M.; Irby, Isaac D.; Alteljevich, Eli; Valle-Levinson, Arnoldo; Wang, Zhengui; Huang, Hai; Shen, Jian; Du, Jiabi
Highlights: Complex physical processes in Chesapeake Bay and the adjacent shelf are investigated by a cross-scale baroclinic model. Recently developed techniques are applied, including a flexible vertical grid system, an implicit transport solver, etc. Good model skills are achieved with the techniques mentioned above and an accurate representation of bathymetry. The importance of bathymetry for estuarine modeling and the effect of bathymetry smoothing are discussed quantitatively. Abstract: We extend the 3D unstructured-grid model previously developed for the Upper Chesapeake Bay to cover the entire Bay and its adjacent shelf, and assess its skill in simulating saltwater intrusion and the coastal plume. Recently developed techniques, including a flexible vertical grid system and a 2nd-order, monotone and implicit transport solver are critical in successfully capturing the baroclinic responses. Most importantly, good accuracy is achieved through an accurate representation of the underlying bathymetry, without any smoothing. The model in general exhibits a good skill for all hydrodynamic variables: the averaged root-mean-square errors (RMSE's) in the Bay are 9 cm for sub-tidal frequency elevation, 17 cm/s for 3D velocity time series, 1.5 PSU and 1.9 PSU for surface and bottom salinity respectively, 1.1  °C and 1.6  °C for surface and bottom temperature respectively. On the shelf, the average RMSE for the surface temperature is 1.4  °C. We highlight, through results from sensitivity tests, the central role played by bathymetry in this estuarine system and the detrimental effects, from a common class of bathymetry smoothers, on volumetric and tracer fluxes as well as key processes such as the channel-shoal contrast in the estuary and plume propagation in the coast.